Large-scale production of paraprobiotic soy milk in stirred tank bioreactor: A dual-step fermentation approach - Chatchol Kongsinkaew; Kant Hongphankul; Thanakorn Soontornkitlert; Worawat Surarit; Manote Sutheerawattananonda; Phongphat Thitasirikul; Soisuda Pornpukdeewattana; Supenya Chittapun; Ketnarin Panpeang; Theppanya Charoenrat (My University, 2024)
This study investigates the feasibility of using soy milk as a substrate for cultivating Lactobacillus casei and its subsequent conversion into paraprobiotics. The research focuses on optimizing the fermentation process from shake flasks to bioreactor scale and assessing the antioxidant properties and proximate compositions of the resulting paraprobiotic soy milk beverage. The study highlights a dual-step large-scale fermentation process comprising an anaerobic fermentation step followed by a thermal inactivation step using the in situ temperature control system of the bioreactor. Results indicated that soy milk enriched with 10 g/L glucose and fermented at 37 °C for 24 h on flask scale provided optimal conditions for L. casei growth, achieving a bacterial count increase of 8.80 ± 0.11 log CFU/mL and a titratable acidity of 0.89 ± 0.03 %. These optimal conditions were employed for bioreactor scale fermentation, attaining a bacterial count of 10.02 ± 0.06 log CFU/mL and a titratable acidity of 1.07 ± 0.04 % at 24 h. The thermal inactivation step at 90 °C for 30 min successfully converted the probiotic soy milk into a paraprobiotic form, maintaining its antioxidant activity at 62.12 ± 2.58 % radical scavenging activity. The final paraprobiotic product met the Food and Drug Administration (FDA) specifications for titratable acidity, presenting a viable alternative for soy-based functional beverages.
Keywords: Titratable acid; Lactobacillus casei; Probiotics and Fermented Foods